2004
DOI: 10.1074/jbc.m309021200
|View full text |Cite
|
Sign up to set email alerts
|

Mutation E252C Increases Drastically the K Value for Na+ and Causes an Alkaline Shift of the pH Dependence of NhaA Na+/H+ Antiporter of Escherichia coli

Abstract: A single Cys replacement of Glu at position 252 (E252C) in loop VIII-IX of NhaA increases drastically the K m for Na ؉ (50-fold) of the Na ؉ /H ؉ antiporter activity of NhaA and shifts the pH dependence of NhaA activity, by one pH unit, to the alkaline range. In parallel, E252C causes a similar alkaline pH shift to the pH-induced conformational change of loop VIII-IX. Thus, although both the Na ؉ /H ؉ antiporter activity of wild type NhaA and its accessibility to trypsin at position Lys 249 in loop VIII-IX inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 50 publications
4
50
0
Order By: Relevance
“…Fig. 2B shows H253C as an example together with the pH profile of the activity of E252C, previously shown to be alkaline shifted by 1 pH unit (16). Hence in this screen, Cys replacements of many residues in the N-terminal half of TMS IX and the vicinal part of loop VIII-IX were found to affect the pH response of NhaA in line with the contention that this NhaA segment participates in the pH sensor.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Fig. 2B shows H253C as an example together with the pH profile of the activity of E252C, previously shown to be alkaline shifted by 1 pH unit (16). Hence in this screen, Cys replacements of many residues in the N-terminal half of TMS IX and the vicinal part of loop VIII-IX were found to affect the pH response of NhaA in line with the contention that this NhaA segment participates in the pH sensor.…”
Section: Resultssupporting
confidence: 58%
“…Notably Cys replacement E252C was shown previously to have an apparent K m for Na ϩ of at least 10 times that of the wild type (Ref. 16 and Table 1). Here we found that Cys replacement L251C (next to Glu 252 ) also increased by 4-fold the apparent K m for Na ϩ of NhaA (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functioning of the protein and its homologues has been a subject of numerous studies during the last decade, as the sodium/proton exchange is crucial in the development of ischemia heart disease and reperfusion (Blatter and McGuigan 1991;Fliegel 1999). While certain functional insights were achieved via biochemical and mutational studies (Gerchman et al 1999;Tzubery et al 2004;Zhang et al 2002), detailed molecular mechanisms of ion transport and regulation of sodium/proton exchange still challenges structural biology. X-ray diffraction on NhaA crystals has recently provided detailed insights into the packing of transmembrane domains (Hunte et al 2005) and, particularly, the architecture of Na + -binding pocket formed by α-helices IV, V and XI (Fig.…”
Section: Probing Molecular Interactions Of Single Membrane Proteinsmentioning
confidence: 99%